Pengaruh Tingkat Pengangguran, Tingkat’pendidikan, Investasi’dan’pertumbuhan’ekonomi’terhadap Kondisi ‘Kemiskinan’di Kabupaten Karangasem - Devi, Krisnina Pradnya; Wenagama, Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 2 (2022): VOL 11 NO 2, FEBRUARI 2022 [405-805]DO - 10.24843/EEP.2022.v11.i02.p03, 2022)
ABSTRACT   Poverty is defined as the inability of the population concerned to achieve or meet a certain minimum standard of living. There are two conditions that cause poverty to occur, namely natural poverty and artificial poverty. Natural poverty occurs, among others, due to limited natural resources, low use of technology and natural disasters. This study aims to analyze the effect of the Unemployment Rate, Education Level, Investment and Economic Growth simultaneously and partially on Poverty Conditions in Karangasem Regency, and to determine the dominant variables that affect the poverty level. The number of samples is 30 years. The data analysis technique used is multiple linear regression analysis. The results showed that the unemployment rate, education level, investment and economic growth had a simultaneous effect on Poverty Conditions. Partially, the unemployment rate has no effect on poverty conditions in Karangasem Regency, while the level of education and investment has a significant negative effect on poverty conditions in Karangasem Regency, and economic growth has a significant positive effect partially on poverty conditions in Karangasem Regency. Keyword : Unemployment, Education, Investment, Ekonomic Growth, Poverty